Tumor Markers in Differential Diagnosis of Benign Ovarian Masses - Li T; Hou N; Mao L; Liu F; Ma Z; Wang L; Xu X; Yan G; Han Y; Wei J (Dove Medical Press, 2024)
Tianlong Li,* Nana Hou,* Lili Mao, Fangmei Liu, Zilong Ma, Li Wang, Xiyue Xu, Guanghui Yan, Yujia Han, Jinxian Wei Department of Gynecology, Zhengzhou First People's Hospital, Zhengzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Jinxian Wei, Email 13700887408@163.comBackground: Although there are many benign tumors in the ovarian adnexal area, the four most common types are still luteal cyst, ovarian mature cystic teratoma (OMCT), ovarian endometriosis, and benign epithelial tumors of the ovary.Purpose: This study aimed to examine the correlation between six tumor markers (CEA, AFP, CA125, CA19-9, SCC, HE4) in the differential diagnosis of female adnexal benign masses and assess their diagnostic value.Patients and Methods: In this study, 135 patients with adnexal benign masses were treated in Zhengzhou first people's Hospital from January 2018 to January 2023. 135 patients were divided into four groups: luteal cyst (13.3%), OMCT (42.2%), ovarian endometriosis (23.7%) and benign epithelial tumors of the ovary (including mucinous cystadenoma and serous cystadenoma) in group D. The receiver-operating characteristic (ROC) curve was used to assess the diagnostic value of each marker and combined detection.Results: The diameter of luteal cysts was significantly smaller than that of benign ovarian tumors (p < 0.001). ROC analysis showed that the combination of AFP, CA125, CA19-9, and SCC had a higher diagnostic rate for luteal cysts (AUC=0.871; sensitivity: 71.8%; specificity: 88.9). The SCC level in OMCT was significantly higher than in other benign ovarian tumors (p=0.007). ROC analysis indicated that the combination of AFP, HE4, and SCC had a higher diagnostic rate for OMCT (AUC=0.753; sensitivity: 65.4%; specificity: 75.4%). The CA125 level in ovarian endometriosis was significantly higher than in other accessory benign tumors (p < 0.001). ROC analysis demonstrated that the combination of AFP, CA125, and CA19-9 had a higher diagnostic rate for ovarian endometriosis (AUC=0.935; sensitivity: 76.7%; specificity: 96.9%). The tumor diameter of benign epithelial tumors of the ovary was significantly larger than that of other benign ovarian tumors (p < 0.001). ROC analysis revealed that the combination of CA125 and CA19-9 had a higher diagnostic rate for benign epithelial tumors of the ovary (AUC=0.792; sensitivity: 64.5%; specificity: 85.7%).Conclusion: The findings of this study demonstrate that the combined use of tumor markers (CEA, AFP, CA125, CA19-9, SCC, and HE4) has value in diagnosing benign ovarian tumors, including luteal cysts, OMCT, ovarian endometriosis, and benign epithelial tumors of the ovary. However, it is important to acknowledge the limitations of this study, which include its single-center nature and the small sample size. Despite these limitations, the results highlight the potential utility of these markers in clinical practice.Keywords: luteal cyst, OMCT, ovarian endometriosis, ovarian epithelial benign tumors, tumor markers